2014
DOI: 10.1371/journal.pone.0110625
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Mitochondrial Genomes of Six Species of Tetranychus Provide Insights into the Phylogeny and Evolution of Spider Mites

Abstract: Many spider mites belonging to the genus Tetranychus are of agronomical importance. With limited morphological characters, Tetranychus mites are usually identified by a combination of morphological characteristics and molecular diagnostics. To clarify their molecular evolution and phylogeny, the mitochondrial genomes of the green and red forms of Tetranychus urticae as well as T. kanzawai, T. ludeni, T. malaysiensis, T. phaselus, T. pueraricola were sequenced and compared. The seven mitochondrial genomes are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 72 publications
1
47
0
1
Order By: Relevance
“…In both these cases, N. namaqua would be incorporated into the respective families, with no resolution to their disparate lifestyle histories. Nuttalliella namaqua may also group basal to the argasid and ixodid families thereby retaining the three tick families as well as the monophyletic nature of the Ixodida, as was observed for 18S, 18S-28S rRNA and mitochondrial genome analysis (Chen et al 2014;Gu et al 2014;Mans et al 2015Mans et al , 2012Mans et al , 2011. Parsimony considerations of the latter position on the tick tree suggest a monophyletic origin for hematophagy in ticks ).…”
Section: The Importance Of N Namaqua In Ancestral Reconstructionmentioning
confidence: 79%
“…In both these cases, N. namaqua would be incorporated into the respective families, with no resolution to their disparate lifestyle histories. Nuttalliella namaqua may also group basal to the argasid and ixodid families thereby retaining the three tick families as well as the monophyletic nature of the Ixodida, as was observed for 18S, 18S-28S rRNA and mitochondrial genome analysis (Chen et al 2014;Gu et al 2014;Mans et al 2015Mans et al , 2012Mans et al , 2011. Parsimony considerations of the latter position on the tick tree suggest a monophyletic origin for hematophagy in ticks ).…”
Section: The Importance Of N Namaqua In Ancestral Reconstructionmentioning
confidence: 79%
“…Maximum likelihood analysis using total mitochondrial nucleic acid data observed the same grouping (Gu et al 2014;Chen et al 2014). Maximum likelihood analysis using a different mitochondrial protein gene set indicated that N. namaqua grouped with the Ixodidae, while the Holothryida as sistergroup to the ticks were replaced by the Mesostigmata (Burger et al 2014).…”
Section: Discussionmentioning
confidence: 84%
“…Analysis of the nuclear 18S rRNA and mitochondrial genes indicated that N. namaqua group basal to the Argasidae and Ixodidae (Mans et al 2011;Mans et al 2012;Gu et al 2014;Chen et al 2014). Other studies using concatenated 18S-28S rRNA gene sets suggested that N. namaqua does not group basal to the other tick families, but shows a closer affinity to the Argasidae , or that its relationship to the other families was unresolved (Burger et al 2014), or that it shows a closer relationship to the Ixodidae using mitochondrial data (Burger et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Further, the complete mitochondrial genome was determined from six species of the genus Tetranychus (Chen et al . ). However, previous studies on the acaroid mites have indicated that ribosomal ITS2 sequences are more conserved than mitochondrial COI sequences (Navajas et al .…”
Section: Introductionmentioning
confidence: 97%